La Comisión del Idioma Oficial (1993-1994): una iniciativa de política lingüística en la postdictadura chilena - Rojas, Darío (2024)
This paper analyzes the initiative to create a Committee for the Official Language (CIO) in Chile between 1993 and 1994. The analysis is based on documents that remain unpublished and almost completely unknown, despite their relevance for the historiography of language policy in post-dictatorial Chile. Taking a glottopolitical approach, we understand the creation of the CIO as an intervention in the public space of language that aims to influence the constitution of the regime of linguistic normativity of the period. In this sense, we will analyze the way in which the CIO proposes a series of options loaded with glottopolitical meanings, such as the selection of Spanish as the official language, and the preference for a certain way of calling the language, among others. These respond to the ideological matrix of Hispanism, from which the ideologemes mobilised in the CIO’s actions and decisions originate, and in relation to which they make sense from a long-term historical perspective.